Experimental study on the effects of rock mineral composition and loading rates on the acoustic emission and fracture characteristics in roof strata tensile fracture - Zhang, Xiufeng; Sun, Jiaxin; Chen, Yang; Wang, Cunwen; Wang, Chao; Ren, Wentao; Ma, Binwen (Frontiers in Earth Science, 2024)
The tensile fracture of the overlying strata in coal mines significantly affects the stability of the surrounding rock and the working face. This study investigates the effects of rock mineral composition and mining speed on roof strata fracture behavior through three-point bending tests under various mineral compositions and loading rates, simulating tensile fractures under different mining conditions. Fracture processes were monitored using an acoustic emission (AE) system and high-speed camera, with multifractal analysis and digital image correlation (DIC) applied to assess AE signal characteristics and crack propagation. Results indicated that siliceous sandstone (SS) exhibited more rapid and penetrating fractures compared to argillaceous sandstone (AS). Before reaching peak load, AS showed a broader multifractal spectrum width (Δα) than SS, reflecting its more ductile fracture behavior, which also resulted in higher Δα values in the post-peak stage. Both Δα and multifractal spectrum difference (Δf(α)) decreased with increasing loading rates for AS, indicating a weakening of the multifractal characteristics of the AE signals and a progressively dominant presence of strong signals. The fracture behavior in both rock types was dominated by tensile microcracks, along with tensile-shear composite and shear microcracks. Higher loading rates increased the proportion of tensile-shear composite and shear microcracks components in the AE signals, with the rate being lower in AS than SS. These findings provide a basis for predicting the characteristics of the tensile fracture of overlying strata in mined-out areas.